Satisfaction P4GN Program of Narcotics National Agency and its Implication of Trust Students in DKI Jakarta - Asmalyah, Susylo; Limakrisna, Nandan (International Review of Management and Marketing, 2019)
The Prevention Program for Eradicating Illicit Abuse and Circulation of Drugs by the National Narcotics Agency in 7 (seven) Private Universities in the Special Capital Region of Jakarta has shown consistency with performance indicators supporting efforts to eradicate drug abuse. The purpose of this study is to improve satisfaction (strategic satisfaction) as a strategic step taken to increase trust in students in the Special Capital Region of Jakarta. And the need to improve Integrated Marketing Communications, Perception Service Quality and Image. The research method used is descriptive survey and explanatory survey. The type of investigation in this study is causality, which is the type of investigation which states that there is a correlation between the independent variables namely integrated marketing communication, service quality and image on satisfaction and its implications for trust in students based on causal relationships. While verification research is to test hypotheses through data collection in the field. The results of data analysis with statistical tests state that integrated marketing communication, perception service quality and image together have a positive and significant effect on satisfaction with a joint contribution of 72%. Keywords: Integrated Marketing Communications, Perception Service Quality, Image, Satisfaction and Trust JEL Classifications: M21, M31, Z33 DOI: https://doi.org/10.32479/irmm.8535